Die verband tussen humorsin en psigologiese welstand by adolessente - Boshoff, Louisa (University of the Free State, 2002)
The aim of this study was to examine the nature of humour and sense of humour, the dynamics of psychological wellbeing as well as adolescence as a critical phase of life, and to determine whether there is an empirical relationship between sense of humour and psychological wellbeing among adolescents. Various theories involving humour and sense of humour were described and a model of humour and sense of humour was developed. In the discussion of psychological wellbeing the relationship with sense of humour was indicated. During the empirical study a cross-sectional survey was held among 884 Grade 12 learners at ten schools in the Pretoria area (Gauteng) and the East London area (Eastern Cape) in respect of sense of coherence, satisfaction with life, fortology/ fortitude, and sense of humour. Sense of coherence was measured by means of Antonovsky's Sense of Coherence questionnaire (SOC: 1987), while satisfaction with life was assessed using the Life Satisfaction Questionnaire (SWLS) of Diener, Emmans, Larson and Griffen (1985), fortology by means of the Fortology Questionnaire (FORQ) developed by Pretorius (1997), and sense of humour was measured by means of the Multidimensional Sense of Humour Scale (MSHS) of Thorson and Powell (1993). Biographical information was obtained by means of a short biographical questionnaire. In this study relatively favourable reliability indicators were obtained for almost all scales and subscales of the measuring instruments used in the research. The current research found that four subscales of humour yielded a statistically significant contribution in the explanation of fortology among adolescents, whereas three of the four subscales, creation of humour, social use of humour and attitude towards humour, yielded a statistically significant contribution in explaining the variance in sense of coherence among adolescents. It would appear from the results that boys show higher levels of sense of humour in terms of the creation of humour and the social use of humour than girls. Considering the interaction between gender and school placement, it is evident that the boys in mixed-gender schools and girls in mixed-gender schools achieved a significantly higher score on the creation of humour as well as the social use of humour than boys in single-gender schools. As far as attitude to humour is concerned, the boys in the single-gender schools returned a significantly lower score than boys in mixed-gender schools and girls in single-gender schools. These findings are related to findings discussed in the literature study. In conclusion proposals are made regarding the use of humour and sense of humour in practice as well as the promotion of psychological wellbeing among adolescents .

Die doel van hierdie ondersoek was om die aard van humor en humorsin, die dinamika van psigologiese welstand en psigologiese weerbaarheid, sowel as adolessensie as 'n kritieke lewensfase, te ondersoek en om vas te stelof daar 'n empiriese verband is tussen humorsin en psigologiese welstand by adolessente. Verskeie teorieë ten opsigte van humor en humorsin is beskryf en 'n model van humor en humorsin is ontwikkel. By die bespreking van psigologiese welstand is daar vanuit die literatuur aangetoon wat die verband is met humorsin. In die empiriese ondersoek is 'n dwarsdeursnitopname gemaak by 884 graad 12- leerders by tien skole in die Pretoria-omgewing (Gauteng) en Oos-London omgewing (Oos-Kaap) oor koherensiesin, lewenstevredenheid, fortologie, en humorsin. Koherensiesin is gemeet deur middel van die Koherensiesinvraelys (SOC) van Antonovsky (1987); lewenstevredenheid deur die Lewenstevredenheidvraelys (SWLS) van Diener, Emmons, Larson en Griffen (1985); fortologie deur die Fortologievraelys (FORO) ontwikkel deur Pretorius (1997) en humorsin is gemeet deur die Multidimensionele humorsinskaal (MSHS) van Thorson en Powell (1993). Biografiese gegewens is deur 'n kort biografiese v~aelys verkry In hierdie ondersoek is relatiewe goeie betroubaarheidsindekse verkry vir feitlik alle skale en subskale van die meetinstrumente wat in die ondersoek gebruik is. Die huidige navorsing het bevind dat vier subskale van humorsin 'n statisties beduidende bydrae lewer in die verklaring van fortologie van adolessente, terwyl drie van die vier subskale, naamlik skep van humor, sosiale gebruik van humor en houding jeens humor, 'n statisties beduidende bydrae in die verklaring van die variansie in koherensiesin van adolessente lewer. Volgens die resultate wil dit verder voorkom of seuns hoër vlakke van humorsin rakende die skep van humor asook sosiale gebruik van humor toon as dogters. Wat die interaksie tussen geslag en skoolplasing betref, blyk dit dat die seuns in die gemengdegeslagskole en dogters in gemengdegeslagskole 'n beduidende hoër telling op die skep van humor sowel as sosiale gebruik van humor as seuns in enkelgeslagskole behaal het. Wat houding jeens humor betref, toon die seuns in die enkelgeslagskole 'n beduidende laer gemiddelde telling as seuns in gemengdegeslagskole en dogters in enkelgeslagskole. Bogenoemde bevindinge word in verband gebring met bevindinge soos in die literatuurstudie bespreek. Ten slotte word voorstelle gemaak ten opsigte van die gebruik van humor en humorsin in die praktyk sowel as die bevordering van psigologiese welstand by adolessente.
Thesis (Ph.D. (Psychology))--University of the Free State, 2002
Keywords: Humour; Sense of humour; Psychological wellbeing; Psychological resilience; Psychofortology; Adolescent psychology; Teenagers -- Conduct of life; Wit and humor -- Psychological aspects